Historia y filosofía de la ciencia como guía para comprender la naturaleza de la ciencia - Niaz, Mansoor (Revista Científica, 2016)
Nature of science (NOS) is considered to be a controversial topic by historians, philosophers of science and science educators. It is paradoxical that we all teach science and still have difficulties in understanding what science is and how it develops and progresses. A major obstacle in understanding NOS is that science is primarily ‘unnatural’, that is it cannot be learned by a simple observation of phenomena. In most parts of the world history and philosophy of science are ‘inside’ science content and as such can guide our understanding of NOS. However, some science educators consider the ‘historical turn’ as dated and hence neglect the historical approach and instead emphasize the model based naturalist view of science. The objective of this presentation is to show that the historical approach is very much a part of teaching science and actually complements naturalism. Understanding NOS generally requires two aspects of science: Domain general and domain specific. In the classroom this can be illustrated by discussing the atomic models developed in the early 20th century which constitute the domain specific aspect of NOS.